A MODERN METHOD IN THE TREATMENT OF MITOCHONDRIAL MYOPATHIES - GENE THERAPY (American Journal of Technology and Applied Sciences, 2023)
In this article, it became known that every healthy person has a 35% chance of having mitochondrial mutations. In order for it to appear, more than 60% of the mitochondria in the cells must have this defect. With our current treatment method, we can save not only patients, but also carriers with gene deletion in their mitochondria, even if the disease does not appear. In particular, in the treatment of myopathies, it is necessary to use not only symptomatic methods, but also genetic engineering methods. Currently, a new method of treating patients with other types of mitochondrial cytopathies is aimed at restoring the structural integrity of mitochondrial genes in the egg cell. With this, we are on the way to improving the health of children who may be born with mitochondrial diseases.